Learning Style Factors in Achieving Mathematical Computational Thinking Ability in Mathematics Education Students - Angraini, Lilis Marina; Arcat; Sohibun (Indonesian Journal of Teaching and Learning, 2024)
Learning styles refer to the methods students use in absorbing and processing information. This study aims to look at learning style factors in the achievement of mathematical computational thinking skills of mathematics education students in the Algebraic Structure course. This research method is a correlational method with a quantitative approach. The research subjects were all mathematics education students who took the Algebraic Structure course in the 2023/2024 academic year as many as 34 students. The data collection methods used include: (1) computational thinking test; (2) questionnaire; and (3) documentation. The research data were processed with the Product Moment correlation statistical test. The results obtained a positive correlation of 0.44 which indicates that there is a positive relationship between learning styles and computational thinking in the observed students. That is, overall, individuals who have a more effective or intensive learning style also tend to have better computational thinking ability.